The Reflection of Family Function and Premarital Sex Behavior on Art Community - Siti Nur Djannah; Bhisma Murti; Yayi Suryo Prabandari; Sapta Anantanyu (Intelektual Pustaka Media Utama, 2016)
The premarital sex behavior in Indonesia based on SKRRI 2012 is a problem which requires the serious concern because it ensues unwanted pregnancy, then take the abortion and carries the venereal disease, therefore the teenager will lose their future. The risk factors related to premarital sex behavior affected by external factor such as the relationship between parents and adolescense. This is occurred in adolescenses who join in an art community of Jathilan, which is Paguyuban Turonggo Wiro Budoyo Wirobrajan Yogyakarta, where the management explains that the members do free sex and they can’t do the family function especially in educating the reproduction health for teenager. This research aims to find out the reflection of family function and reproduction health of and sex in teenager of TWB Community.This research is quantitative descriptive support by qualitative. The data collecting technique is purpose sampling. The research subject is Community members of Seni Jathilan Turongo Wiro Budoyo, total 47 members. The reflection of family function in teenager of TWB community member, majority of family don’t give the education function, affection function, protection function, and socialization function adolescense reproduction health, and the reflection teenager sex of TWB Community is majority doing free sex.